Nutrient accumulation models in the banana (Musa AAA Simmonds cv Williams) plant under nitrogen doses - Jaime Torres Bazurto; Jaiver Danilo Sanchez; Daniel Gerardo Cayon Salinas (Acta Agronómica)
This research determined the effect of four nitrogen (N) doses on the nutritional behavior of (N), potassium (K), phosphorus (P), calcium (Ca) and magnesium (Mg), respectively, in banana Williams, during five plant development stages and two productive cycles. The treatments were as follows: 1) absolute control, 2) 0 N, 3) 161 kg N ha-1, 4) 321.8 kg N ha-1 and 5) 483 kg N ha-1, respectively. A multivariate approach of the differences among cycles was used to adjust the models and eliminate their individual effect, with a randomized complete block design with repeated measurements over time. There were significant differences among plant development stages, with an increase in nutrient accumulation in the banana plant, there were no differences among treatments or blocks, nor in the interaction block by treatment, but the dose of 321.8 kg of N, exhibited a fructification increase in terms of N accumulation, harvest was exceeded by the dose of 483 kg of nitrogen, Ca and Mg, were the other nutrients, which showed effect at the dose of 483 kg of N but increasing only to harvest. It was concluded that high doses of nitrogen showed a trend to increase nutrient accumulation during the development of the banana plant, but especially until fructification, with the exception of Ca and Mg, which achieved the greatest accumulation in harvest.